Parking Generation by â€œPharmacyâ€ Land Use Type in Johor Bahru, Malaysia (Jurnal Teknologi (Sciences & Engineering), 2014)
Transportation planners need prior data on "Parking Generations" for new developments and to predict changes in the parking generation due to modifications in the existing land use types. Parking Generations depends on various factors including the socioeconomic characteristics. The Institute of Transportation Engineers (ITE) is an international body of transport professionals that publishes and updates the information on parking generation for various land use types in USA. In Malaysia, no parking generation guidebook exists. Transport planners in Malaysia have to depend on the parking generation data and models developed based on other countries which may be misleading and inaccurate. The ITE provides parking generation data for 106 different land use types including â€œPharmacyâ€. The objective of the paper is to study the parking generation rate for the land use type "Pharmacy" and develop regression models for predicting daily parking generation by pharmacies based on the Johor Bahru environment in Malaysia. Data were collected from the selected thirteen (13) pharmacy locations in Johor Bahru area. The data collection also included a survey of stakeholders including information on a) gross floor space area b) available parking spaces adjacent to the pharmacy c) presence of similar pharmacies in the vicinity (500 m radius). Linear regression models were developed to predict peak hour parking generations by the â€œPharmacyâ€ land use type. The developed models are recommended to be used by the professionals for the Malaysian local environment.